2016
DOI: 10.2217/pme-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Polymorphisms Associated with Hyperuricemia or Gout in the Hmong

Abstract: Aim Hyperuricemia commonly causes gout. Minnesota Hmong exhibit a two- to fivefold higher prevalence of gout versus non-Hmong. To elucidate a possible genomic contribution to this disparity, prevalence of risk alleles for hyperuricemia in Hmong was compared with European (CEU) and Han-Chinese (CHB). Methods In total, 235 Hmong were genotyped for eight SNPs representing five candidate genes (SLC22A12, SLC2A9, ABCG2, SLC17A1 and PDZK1). Results The frequency of seven out of eight risk alleles in the Hmong wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…1702M06041), took place from April to August 2017. Detailed methods describing recruitment, consent, genomic DNA collection, genotyping, and genotype analysis are described in previous publications 15, 26 . All the information required for this project was collected during the respective study periods under the supervision of University of Minnesota Institutional Review Board (UMN IRB) complying with ethical standards in the conduction of research with human subjects.…”
Section: Methodsmentioning
confidence: 99%
“…1702M06041), took place from April to August 2017. Detailed methods describing recruitment, consent, genomic DNA collection, genotyping, and genotype analysis are described in previous publications 15, 26 . All the information required for this project was collected during the respective study periods under the supervision of University of Minnesota Institutional Review Board (UMN IRB) complying with ethical standards in the conduction of research with human subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, these initial studies are clearly of a Bdiscovery^nature and findings from them would be considered only hypothesis generating. Of interest, both the results summarized in this paper and that of Roman et al 2016, identify important differences in allele frequencies of SNPs governing predicted drug dosage (for warfarin) and risk for medical problems (such as hyperuricemia and gout) between the Hmong and other Asian populations. Given that these investigations are hypothesis generating at this stage, the Board ultimately decided to accept the IRB limitation, work to minimize the community concerns by explaining general results, and resolve to conduct future studies with genetic counselors so the IRB would allow us to give individual results to participants who wanted them.…”
Section: Discussionmentioning
confidence: 85%
“…Still other members of the Board felt that there was enough uncertainty in the findings to not contest the IRB decision, noting that our findings of the genetic risks for cardiovascular diseases would have limited predictive power and that genotypes predicting potential altered drug metabolism would need to be validated before any formal interpretation could be considered (Relling and Klein 2011). Subsequent suspected genomic sources of contribution to other medical problems-specifically hyperuricemia and gout, which were of significant interest to our Hmong community members-were conducted utilizing this same sample population and sources of genomic DNA (Roman et al 2016). Indeed, these initial studies are clearly of a Bdiscovery^nature and findings from them would be considered only hypothesis generating.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified a statistically higher prevalence of validated risk alleles in the US Hmong population compared with published data on people of European or Chinese ancestry. Specifically, six out of eight risk alleles were more prevalent in the Hmong than Europeans, and two out of three risk alleles were more prevalent in the Hmong than the Chinese [29]. This observation represents the genetic basis for the higher prevalence of hyperuricemia and gout in the Hmong.…”
Section: Hmong-related Health Issuesmentioning
confidence: 80%